Microdeletion 5q14.3 and anomalies of brain development. Issue 9 (4th July 2013) - Hotz, Alrun; Hellenbroich, Yorck; Sperner, Jürgen; Linder‐Lucht, Michaela; Tacke, Uta; Walter, Caren; Caliebe, Almuth; Nagel, Inga; Saunders, Dawn E.; Wolff, Gerhard; Martin, Peter; Morris‐Rosendahl, Deborah J.
Abstract: 5q14.3 deletions spanning and flanking MEF2C as well as intragenic MEF2C mutations have recently been described as a cause of severe intellectual disability, epilepsy, and muscular hypotonia, with variable brain and other anomalies. With an increasing number of patients described, the clinical presentation of the patients appears to be relatively uniform, however the structural brain phenotypes described are variable. We describe two unrelated patients with overlapping de novo interstitial deletions of 4.1 and 1.9 Mb, including MEF2C in 5q14.3, one of whom had a complex brain malformation which could be best described as microcephaly with simplified gyral pattern (MSG). Expression analysis in both patients confirmed haploinsufficiency for MEF2C, decreased MECP2 expression and increased C3ORF58 ( DIA1 ) expression, which is a new finding. A detailed analysis of brain and white matter abnormalities reported in patients with 5q14.3 deletion syndrome to date revealed a greater number of reported abnormalities in patients with deletions not including MEF2C than those with deletions or mutations directly affecting MEF2C . Screening an additional 43 patients with malformations of cerebral cortical development (MCD) for mutations in MEF2C and/or deletions in 5q14.3q15, did not detect any additional mutations, allowing us to conclude that 5q14.3 deletion syndrome is a rare cause of microcephaly with simplified gyral pattern. © 2013 Wiley Periodicals, Inc.